철근공사의 코일철근(Bar in Coil) 적용타당성 분석 - 이현수; 김재곤; 박문서; 김현수; 황성주; Lee, Hyun-Soo; Kim, Jae-Gon; Park, Moon-Seo; Kim, Hyun-Soo; Hwang, Sung-Joo (한국건설관리학회 논문집, 13(1), 2012)
The proportion of rebar factory manufacturing which has been settled down in Korea recently seems to increase because of their strength such as high decreasing rate of rebar loss and manufacturing accuracy and the external factors such as an increase of downtown projects and a decrease of skilled workers. However, factory manufacturing using straight rebars causes a certain amount of rebar loss and an environmental problem including $CO_2$ emissions. To solve these problems, Bar in coil (BIC) has been introduced; however its application is very rare because it has not been produced so far in Korea and manufacturing machines of BIC are very expensive. Also, although BIC's application is expected to expand due to its strengths, few analysis of its application has been conducted. Therefore in this study, analysis of the BIC's characteristics and the influence to the rebar manufacturing industry are conducted for the advancement of rebar work as a basic research. To achieve this, inquiry on the present condition of rebar manufacturing industry in Korea is implemented. Then, the validation of BIC's applications by aspects of industry and the analysis of stakeholders' economical profit and loss are conducted. 최근 국내에서 정착되고 있는 철근 공장가공은 절단손실 감소, 정밀도 향상 등의 장점과 도심지공사 증가, 숙련공 감소 등의 외부 요인으로 향후 비중이 증가할 것으로 예상된다. 그러나 공장가공을 하더라도 정척철근 (Straight rebar)을 사용하면 손실 발생 및 그로 인한 CO2배출 같은 환경 문제가 발생할 수밖에 없다. 이를 해결하기 위한 대안의 일환으로 코일철근(Bar in coil) 도입이 제안되었으나, 코일철근은 국내 미생산, 고가의 장비비 등의 이유로 국내 적용이 거의 전무하다. 또한 코일철근은 완전 자동화에 가까운 방식으로 가공되기 때문에 향후 높은 손실저감률과 가품질이 우수하여 국내 적용이 확대될 것으로 예상되나, 적용타당성 분석에 대한 연구가 부족한 실정이다. 따라서 본 연구에서는 최근 국내 생산이 시작된 코일철근의 특성과 코일철근 도입이 철근가공 산업에 미치는 영향을 분석, 철근가공 산업 선진화를 위한 기초연구로서 진행한다. 이를 위해 국내 철근가공 산업의 현황을 조사하고, 코일철근 도입시 산업적 측면에서 적용성과 경제적 측면에서 이해관계자의 손익 타당성을 분석하고 향후 연구방향을 제시한다.